Effectiveness of sensorimotor training on pain, cervical joint position sense, range of motion, balance, and disability in chronic neck pain: A systematic review - Sahar Zaidi; Sohrab Ahmad Khan; Saima Zaki; Habiba Sundus; Md Farhan Alam; Shibili Nuhmani (Heliyon)
Background: Chronic neck pain is a prevalent condition with multifactorial etiology, significantly impairing quality of life and increasing healthcare burdens. Sensorimotor training (SMT) is a targeted intervention addressing proprioceptive deficits, cervical range of motion (CROM), balance, and disability. Objective: To systematically evaluate the effectiveness of SMT in improving pain, cervical joint position sense (CJPS), CROM, balance, and disability in patients with chronic neck pain. Methods: This systematic review followed PRISMA guidelines and included 10 randomized controlled trials (RCTs) sourced from PubMed, Scopus, and Web of Science, covering literature from inception to August 2024. Studies involving adult participants with chronic neck pain of at least three months, assessing SMT protocols against control or traditional treatments, were included. Data extraction covered sample characteristics, intervention details, and outcomes. Methodological quality was evaluated using the PEDro scale, with a minimum score of 6, and risk of bias was assessed using the RoB 2.0 tool. Studies were subjected to a narrative synthesis due to heterogeneity in protocols and outcome measures. Results: SMT significantly reduced pain, improved CJPS, enhanced CROM, and boosted balance and functional outcomes across diverse protocols. Combined SMT approaches targeting proprioception, oculomotor control, and balance produced sustained benefits over 12 months. Long-term improvements included enhanced postural stability, reduced joint position error, and decreased disability. Methodological quality of included studies was moderate to high, with several studies achieving long-term outcome sustainability. Conclusion: SMT is an effective intervention for chronic neck pain, addressing pain, sensorimotor deficits, balance impairments, and disability. While variability in protocols highlights the need for standardization, findings underscore the potential of SMT as an adjunct to traditional therapies. Future research should explore standardized protocols, advanced technologies, and diverse populations.